2020
DOI: 10.3390/su12229549
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Strategies for Implementing Education for Sustainable Development in the UK Primary Schools: A Service Innovation Perspective

Abstract: Education for sustainable development (ESD) in schools requires a whole-school approach to ensure that all stakeholders, including students, value sustainability and express this value in an active engagement in the ongoing development process. Such inclusivity however is rarely achieved, with benefits of ESD in schools usually recognised only by a select few. School strategies that continue to dominate research focus on management of the finite resources or give emphasis to a particular pedagogical agenda, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The overarching aspect of effective ESD in schools is determined by the effectiveness of the role of the school leaders. Educational research has identified the importance of school leaders in ESD for the successful and longterm implementation of educational innovations (Kadji-Beltran et al, 2012;Mogren & Gericke, 2019;Kuzmina et al, 2020). However, school leaders' actions as crucial players in managing and coordinating ESD have not been empirically discovered (Leithwood et al, 2004;Leithwood & Jantzi, 2005).…”
Section: Esd and School Leadershipmentioning
confidence: 99%
“…The overarching aspect of effective ESD in schools is determined by the effectiveness of the role of the school leaders. Educational research has identified the importance of school leaders in ESD for the successful and longterm implementation of educational innovations (Kadji-Beltran et al, 2012;Mogren & Gericke, 2019;Kuzmina et al, 2020). However, school leaders' actions as crucial players in managing and coordinating ESD have not been empirically discovered (Leithwood et al, 2004;Leithwood & Jantzi, 2005).…”
Section: Esd and School Leadershipmentioning
confidence: 99%
“…There is also evidence that very few studies have conceptualized the implementation of ESD at an organizational level, an area of research that continues to be poorly investigated (Kuzmina et al, 2020). A study by M€ uller et al (2021) in schools in Germany, Macau, and the US shows that empirical data on ESD are relatively scarce.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…There is also evidence that very few studies have conceptualized the implementation of ESD at an organizational level, an area of research that continues to be poorly investigated (Kuzmina et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the global encouragement for ESD and the acknowledgment of the school principal's role as a critical component in ESD implementation, research on the latter is still at an early stage (Verhelst et al, 2021). There is also evidence that very few studies have conceptualized the implementation of ESD at an organizational level, an area of research that continues to be poorly investigated (Kuzmina et al, 2020). QRJ 24,4…”
Section: Introductionmentioning
confidence: 99%